2019
DOI: 10.1002/ajoc.201900118
|View full text |Cite
|
Sign up to set email alerts
|

Phenyliodonium Diacetate Mediated Carbotrifluoromethylation of Quinoxalin‐2(1H)‐ones

Abstract: An efficient method for the synthesis of 3trifluoromethylquinoxalin-2(1H)-ones by a direct trifluoromethylation of quinoxalin-2(1H)-one derivatives has been developed under transition-metal-free conditions. The strategy uses cheap and commercially available PhI(OAc) 2 as a promoter, TMSCF 3 as a trifluoromethylation reagent in the presence of catalytic amount of benzoquinone to give the products in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…After this pioneering work of C3 trifluoromethylation on quinoxalin-2(1H)-ones with CF 3 SO 2 Na, various reports were published on the generation of this moiety. In 2019, Hu & group [26] established an oxidative CÀ H trifluoromethylation of quinoxalinones using TMSCF 3 as the trifluoromethylating reagent. They used PhI(OAc) 2 as the oxidant in the presence of a catalytic amount of benzoquinone (BQ) and KF as the additive in the argon atmosphere (Scheme 3).…”
Section: Trifluoromethylation Of Quinoxalin-2(1h)-onesmentioning
confidence: 99%
“…After this pioneering work of C3 trifluoromethylation on quinoxalin-2(1H)-ones with CF 3 SO 2 Na, various reports were published on the generation of this moiety. In 2019, Hu & group [26] established an oxidative CÀ H trifluoromethylation of quinoxalinones using TMSCF 3 as the trifluoromethylating reagent. They used PhI(OAc) 2 as the oxidant in the presence of a catalytic amount of benzoquinone (BQ) and KF as the additive in the argon atmosphere (Scheme 3).…”
Section: Trifluoromethylation Of Quinoxalin-2(1h)-onesmentioning
confidence: 99%
“…Soon afterwards, in March 2019, Xue et al reported a method to synthesize 3-trifluoromethylquinoxalin-2(1 H )-ones with (trifluoromethyl)trimethylsilane (Ruppert-Prakash reagent) as a trifluoromethyl source under transition metal-free conditions ( Figure 1B , Equation d) (Xue et al, 2019a ). This protocol has the advantages of using cheaper (diacetoxyiodo)benzene(PhI(OAc) 2 )compared with PhI(OTFA) 2 as an oxidant and stable (trifluoromethyl)trimethylsilane as the trifluoromethyl source.…”
Section: C–h Trifluoromethylation Of Quinoxalin-2(1 H mentioning
confidence: 99%
“…Because of their synthetic usefulness and potential biological importance, the introduction of functional groups into the C3-position of the quinoxalin-2(1 H )-ones has already become a research hotspot, and various protocols for the direct C3-H functionalization of quinoxalin-2(1 H )-ones have been reported (Ebersol et al, 2019 ; Gu et al, 2019 ; Hong et al, 2019 ; Li et al, 2019 ; Peng et al, 2019 ; Rostoll-Berenguer et al, 2019 ; Teng et al, 2019 ; Wang et al, 2019a , 2020 ; Xie et al, 2019b ; Zhao et al, 2019 ; Zheng and Studer, 2019 ; Tian et al, 2020 ; Yuan et al, 2020 ). In particular, the C3-H functionalization of quinoxalin-2(1 H )-ones involving hypervalent iodine reagents has drawn wide attention for the aforementioned advantages of hypervalent iodine reagents, mainly including arylation (Paul et al, 2017 ; Yin and Zhang, 2017 ), trifluoromethylation (Wang et al, 2018 ; Xue et al, 2019a ), alkylation (Wang et al, 2019b ; Xie et al, 2019a ; Xue et al, 2019b ; Shen et al, 2020 ), and alkoxylation (Xu et al, 2019 ; Yang et al, 2019 ) of quinoxalin-2(1 H )-ones, which provide convenient and environmentally friendly means for the synthesis of 3-substituted quinoxalinone derivatives. In this mini review, we will focus on the progress being made in the direct C3-H functionalization of quinoxalin-2(1 H )-ones involving the hypervalent iodine reagents and discuss their mechanisms, in order to inspire more applications of hypervalent iodine reagents in related reactions.…”
Section: Introductionmentioning
confidence: 99%
“…65,156.44,140.35,133.36,131.31,129.00,128.83,115.80,53.81,40.85,33.45,20.31,20.13,19.45,14.19. HRMS (ESI): Calculated for C 15…”
Section: -(1-azidopentan-2-yl)-7-bromo-1-methylquinoxalin-2(1h)one (mentioning
confidence: 99%
“…13 C NMR (126 MHz,CDCl 3 ) δ 159.93,154.64,133.01,132.52,130.25,130.14,123.73,113.66,53.37,41.82,33.49,32.63,29.92,29.24,25.60. HRMS (ESI): Calculated for C 15 7.59-7.54 (m, 1H), 7.38-7.34 (m, 1H), 7.32 (dd, J = 8.4, 1.4 Hz, 1H), 4.03 (t, J = 6.6 Hz, 2H), 3.86 (dd,J = 11.8,8.2 Hz,1H),3.72 (m,4H),3.60 (dd,J = 11.8,5.5 Hz, 1H), 3.07 (td, J = 8.6, 1.1 Hz, 1H), 2.26-2.18 (m, 2H), 2.15-2.12 (m, 1H), 1.96-1.83 (m, 3H), 1.70 (ddd, J = 10.6, 5.2, 2.7 Hz, 2H), 1.67-1.63 (m, 2H), 1.44-1.34 (m, 2H). 13 C NMR (126 MHz, CDCl 3 ) δ 175.…”
Section: -(1-azido-6-hydroxyhexan-2-yl)-1-methylquinoxalin-2(1h)one mentioning
confidence: 99%